The Effectiveness of Incubator Humidity Education on Nurse's Knowledge, Attitude, and Skills in Perinatology Room - Ompusunggu, Fransiska; Rustina, Yeni; Efendi, Defi (Universitas Prima Indonesia, 2024)
Newborns, especially premature infants, are at high risk of ineffective thermoregulation due to their less complex skin structure. Impaired thermoregulation experienced by premature infants can lead to hypothermia. Premature infants who experience hypothermia can cause complications that have the potential to cause disability and death. One of the efforts to prevent hypothermia is to place premature infants in an incubator that gives moisture so that moisture regulation is needed to help regulate the baby's temperature, especially in premature infants who experience ineffective thermoregulation. Humidity regulation is required for the incubator to prevent fluid loss through evaporation. This study aims to determine the effectiveness of providing incubator humidity education on nurses' knowledge, attitudes, and skills in the Perinatology room. The research design used a pre-experimental group without control with an accidental sampling technique; namely, there was a pre-test before and a post-test after treatment. Thus, the treatment results can be more accurate because they can be compared with the situation before treatment. This study involved 37 respondents in the perinatology room in one of the state hospitals using pre-and post-test questionnaires conducted from April to May 2022. The results showed that there were significant differences before and after education on knowledge (p=0.001), attitudes (p=0.001), and skills (p=0.001). The results of this study can used as a reference in developing standard procedures for incubator humidity to prevent ineffective thermoregulation in premature infants through cognitive improvement of nurses about incubators.